Alpha-1 antitrypsin in COVID-19 patients: a dual-center screening study in Malaysia - Norsyuhadah Musa; Wan Norlina Wan Azman; Nor Amirah Mohammad Nazri; Tuan Salwani Tuan Ismail; Azian Harun; Najib Majdi Yaacob; Sarina Sulong; K.N.S Sirajudeen; Mahaya Che Mat; Hani Ajrina Zulkeflee (King Faisal Specialist Hospital and Research Centre, 2026)
Indexed by WOS / SCOPUS / ERA